2021
DOI: 10.21037/atm-20-6049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tumor mutation burden combined with immune infiltrates in endometrial cancer

Abstract: Background: Tumor mutational burden (TMB) is widely regarded as a predictor of response to immunotherapy. Few researchers have focused on the activity and prognosis of TMB in endometrial cancer (EC) and immune cells. Our study aimed to identify the prognostic role of TMB in EC.Methods: We downloaded transcriptome data from The Cancer Genome Atlas (TCGA) database. Kaplan-Meier analysis with log-rank test was conducted to assess the difference in overall survival (OS) between the high and low TMB groups. The "CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…Previous studies have indicated that increased infiltration of intratumoral CD8 + T cells is associated with a better prognosis in different cancer types (36)(37)(38), and a recent study based on multiplex immunofluorescent assays further supported the prognostic value of tumor infiltrating T cells in early-stage endometrial cancer (39). In this study, we also observed relatively high percentages of CD8 + T cells in samples of TMB-H EC, which is believed to have a favorable survival outcome (23). However, studies have shown that the functional status of CD8 + T cells changes with tumor progression, and different stages of dysfunctional T cells, characterized by the expression of specific immune checkpoint molecules, are thought to be associated with distinct response rates to immune checkpoint inhibitors (40).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have indicated that increased infiltration of intratumoral CD8 + T cells is associated with a better prognosis in different cancer types (36)(37)(38), and a recent study based on multiplex immunofluorescent assays further supported the prognostic value of tumor infiltrating T cells in early-stage endometrial cancer (39). In this study, we also observed relatively high percentages of CD8 + T cells in samples of TMB-H EC, which is believed to have a favorable survival outcome (23). However, studies have shown that the functional status of CD8 + T cells changes with tumor progression, and different stages of dysfunctional T cells, characterized by the expression of specific immune checkpoint molecules, are thought to be associated with distinct response rates to immune checkpoint inhibitors (40).…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with TCGA data (1), patients with POLE mutations showed the highest level of TMB, followed by the MSI-H subtype, NSMP, and TP53 mutant subtypes (Figure 2). Recent studies have indicated that TMB is highly associated with tumor-infiltrating immune cells, PD-L1 expression, and patients' prognosis in both endometrial cancer and other cancer types (23)(24)(25). Additionally, considering the relatively small sample size of the POLE mutant and MSI-H subtypes, we combined the two subtypes into the TMB high (TMB-H) subtype in the following analysis.…”
Section: Tmb Levels Of Different Molecular Subtypes Of Ecmentioning
confidence: 99%
“…The higher TMB and PD-L1 expression in MSI-H and MMRd endometrial tumors support the clinical efficacy of PD-1 inhibitors in treating solid tumors with MMRd (112). Moreover, as mentioned earlier, PD-L1 expression increased with TIL abundance in the EC ITME, indicating that PD-1 inhibitors can induce an effective anti-tumor immune response in EC with high PD-L1 expression (104)(105)(106). In 2017, the FDA approved pabolizumab for the treatment of solid tumors with unresectable or metastatic MSI-H or MMRd.…”
Section: Immunotherapy In Ecsupporting
confidence: 73%
“…According to the TCGA data, patients with POLE mutations showed the highest tumor mutation burden (TMB), followed by those with the MSI-H subtype. Reports have illuminated that TMB is highly associated with tumorinfiltrating immune cells, PD-L1 expression and patients' prognosis in EC (104)(105)(106). Meanwhile, studies have also reported that POLEmut and MMRd EC have a high number of CD8+ CTLs expressing PD-1 (29).…”
Section: Itme In Different Subtypes Of Ecmentioning
confidence: 99%
“…[ 13–15 ]. Recently, the role of TMB combined with immune infiltration in endometrial cancer was studied [ 16 ]. Micro ribonucleic acid (miRNA) is a type of non-coding RNA fragment that has the function of regulating the expression of post-transcribed genes.…”
Section: Introductionmentioning
confidence: 99%